Polygenic Risk Score of Adolescent Idiopathic Scoliosis for Potential Clinical Use. (22nd June 2021) - Otomo, Nao; Lu, Hsing‐Fang; Koido, Masaru; Kou, Ikuyo; Takeda, Kazuki; Momozawa, Yukihide; Kubo, Michiaki; Kamatani, Yoichiro; Ogura, Yoji; Takahashi, Yohei; Nakajima, Masahiro; Minami, Shohei; et al.
ABSTRACT: Adolescent idiopathic scoliosis (AIS) is a common disease causing three‐dimensional spinal deformity in as many as 3% of adolescents. Development of a method that can accurately predict the onset and progression of AIS is an immediate need for clinical practice. Because the heritability of AIS is estimated as high as 87.5% in twin studies, prediction of its onset and progression based on genetic data is a promising option. We show the usefulness of polygenic risk score (PRS) for the prediction of onset and progression of AIS. We used AIS genomewide association study (GWAS) data comprising 79, 211 subjects in three cohorts and constructed a PRS based on association statistics in a discovery set including 31, 999 female subjects. After calibration using a validation data set, we applied the PRS to a test data set. By integrating functional annotations showing heritability enrichment in the selection of variants, the PRS demonstrated an association with AIS susceptibility ( p  = 3.5 × 10 −40 with area under the receiver‐operating characteristic [AUROC] = 0.674, sensitivity = 0.644, and specificity = 0.622). The decile with the highest PRS showed an odds ratio of as high as 3.36 ( p  = 1.4 × 10 −10 ) to develop AIS compared with the fifth in decile. The addition of a predictive model with only a single clinical parameter (body mass index) improved predictive ability for development of AIS (AUROC = 0.722, net reclassification improvement [NRI] 0.505 ± 0.054, p  = 1.6 × 10 −8 ), potentiating clinical use of the prediction model. Furthermore, we found the Cobb angle (CA), the severity measurement of AIS, to be a polygenic trait that showed a significant genetic correlation with AIS susceptibility (rg = 0.6, p  = 3.0 × 10 −4 ). The AIS PRS demonstrated a significant association with CA. These results indicate a shared polygenic architecture between onset and progression of AIS and the potential usefulness of PRS in clinical settings as a predictor to promote early intervention of AIS and avoid invasive surgery. © 2021 American Society for Bone and Mineral Research (ASBMR).